The Significance of Encoding and Decoding Mechanisms in Language Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines theories on the essential nature of culture and linguistic communication within the context of language teaching. Communication is a dynamic and evolving process that undergoes continual adaptation over time dynamics introduce a range of challenges and intrigue to the learning process. Language education encompasses both verbal and non-verbal aspects of communication, often posing difficulties for learners in understanding idioms, euphemisms, cultural gaps (lacunae), and discourse patterns of the target nation. Learners frequently face confusion and misinterpretation when navigating unfamiliar situations in the target language, struggling with the concepts of message encoding and decoding. All these factors prove the importance of studying intercultural communication in language learning. The research includes an introduction, methodology, result, and discussion stages where recent sources from online and offline platforms were implemented. In addition, some conclusions from the author’s experiences were analyzed and discussed. Encoding occurs naturally and unconsciously within members of the same society, while decoding takes place between speakers of different linguistic and cultural backgrounds. Both processes demand an understanding of the culture, history, traditions, and religion of the respective society. These elements highlight the critical importance of studying intercultural communication in language learning.The research incorporates an introduction, methodology, results, and discussion, utilizing recent sources from both online and offline platforms. Additionally, the author’s personal experiences and observations were analyzed and discussed to draw meaningful conclusions.